Person-Centered Leadership: The Practical Idea as a Dynamic Principle for Ethical Leadership - Murcio, Ricardo; Scalzo, Germán (Frontiers in Psychology, 2021)
In search of ethical conceptual frameworks that are applicable to the practical reality of companies, ethical leadership has recently gained ground in Business Ethics scholarship as a broad umbrella under which to fit both normative and descriptive approaches to management. This article delves into Carlos Llano's seminal studies in the field, and his rediscovery of the “practical idea” as a dynamic principle for integrating the practice of management and ethical leadership in light of a realistic personalism. Llano was one of the first authors to study the firm from a humanistic, people-centered perspective as a “community or people,” and his view of practical wisdom is an effort to integrate this intellectual virtue with human will by offering a personalist open dynamism that is at the center of all relationships at work, allowing those involved to grow therein. Hence, his notion of the practical idea is his most original contribution to the promotion of managerial action as a catalyst for person-centered leadership.